The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/1678-4685-gmb-2020-0050
|View full text |Cite|
|
Sign up to set email alerts
|

Long noncoding RNA POU6F2-AS1 regulates lung cancer aggressiveness through sponging miR-34c-5p to modulate KCNJ4 expression

Abstract: It has been extensively reported that long noncoding RNAs (lncRNAs) were closely associated with multiple malignancies. The aim of our study was to investigate the effects and mechanism of lncRNA POU6F2-AS1 in lung adenocarcinoma (LADC).The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) datasets provided us the information of LADC clinical samples. High-regulation of POU6F2-AS1 was presented in LADC tissues compared with adjacent normal tissues, which was correlated with poor outcome of LADC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Kir2.1(KCNJ2) is associated with the development of papillary thyroid carcinoma(PTC), and interference with KCNJ2 inhibits cell proliferation, invasion, migration, and EMT processes ( 38 ). The researchers found that the lncRNA POU6F2-AS1 may act as a competitive endogenous RNA(ceRNA) for miR-34c-5p and promote the expression of Kir2.3(KCNJ4) and enhance the invasiveness of LC cells ( 39 ). Kir6.2(KCNJ11) and Sulfonylurea Receptor(ABCC9) gene expression is downregulated in OC compared to healthy tissues, and expression of Kir6.2 correlates with OC prognosis ( 40 ).…”
Section: Relationship Between Potassium Channel and Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…Kir2.1(KCNJ2) is associated with the development of papillary thyroid carcinoma(PTC), and interference with KCNJ2 inhibits cell proliferation, invasion, migration, and EMT processes ( 38 ). The researchers found that the lncRNA POU6F2-AS1 may act as a competitive endogenous RNA(ceRNA) for miR-34c-5p and promote the expression of Kir2.3(KCNJ4) and enhance the invasiveness of LC cells ( 39 ). Kir6.2(KCNJ11) and Sulfonylurea Receptor(ABCC9) gene expression is downregulated in OC compared to healthy tissues, and expression of Kir6.2 correlates with OC prognosis ( 40 ).…”
Section: Relationship Between Potassium Channel and Tumormentioning
confidence: 99%
“…Kir2.1 is highly expressed in GC and is positively correlated with depth of tumor invasion, metastatic status, and poor overall patient survival, and is a potential prognostic marker and therapeutic target ( 64 ). Kir2.3 overexpression is strongly associated with poor prognosis in patients with LUAD ( 39 ). In OC, minoxidil prevents tumor growth in OC xenograft models by stimulating Kir6.2/SUR2 channels to produce mitochondrial destruction and extensive DNA damage, altering the metabolic and oxidative status of cancer cells ( 40 ).…”
Section: Role Of Potassium Channel In Diagnosis and Treatment Of Tumormentioning
confidence: 99%
“…Another Kir2 channel, KCNJ4 (Kir2.3), is also modulated by lncRNA. In human lung adenocarcinoma Calu-3 and NCI-H460 cell lines, lncRNA POU6F2-AS1 can sponge miR-34c-5p and facilitate KCNJ4 expression, promoting the development of lung adenocarcinoma cells [179] .…”
Section: Lncrnas and Lipid Signalingmentioning
confidence: 99%